On omega-Connectedness and omega-Continuity in the Product Space (European Journal of Pure and Applied Mathematics, 2018)
In this paper, the concepts of $ω$-open and $ω$-closed functions between topological spaces will be introduced and characterized. Moreover, related concepts such as $ω$-connectedness and $ω$-continuity from an arbitarary topological space into the product space will also be characterized.
Keywords: $ω$-open; $ω$-closed; $ω$-connected; $ω$-continuous